Mass spectrometric profiling of microbial polysaccharides using laser desorption/ionization – time-of-flight (LDI-TOF) and liquid chromatography-mass spectrometry (LC-MS): a novel method for structural fingerprinting and derivatization - Dadovska, Lucia; Paskova, Veronika; Novak, Petr; Hrabak, Jaroslav (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionOver the last two decades, matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) has been introduced into the routine diagnostic practice of microbiological laboratories for the rapid taxonomic identification of bacteria and yeasts. However, a method that effectively identifies microbes directly from clinical samples using MALDI-TOF MS has not yet been found. One of the promising targets is microbial polysaccharides, which are abundant structures in bacterial and fungal cells. Their rapid and inexpensive analysis, nevertheless, is complicated. This study focused on detecting microbial polysaccharides, such as lipopolysaccharides, using MALDI-TOF MS and liquid chromatography-tandem mass spectrometry (LC-MS). We developed a method for fingerprinting polysaccharides by acid hydrolysis and enzymatic digestion.MethodsThe mono- and oligosaccharides are then derivatized with a newly designed probe (vanillyl pararosaniline, the HD ligand), enabling efficient ionization without the use of the MALDI matrix. For precise analysis of polysaccharides, the hydroxyl groups can be esterified by formic acid.ResultsThe method was validated using several saccharides as well as Escherichia coli lipopolysaccharides (O26:B6, O55:B5, and O111:B4). Derivatization using the HD ligand also allows the detection of structures containing amines and phosphate groups in positive ion mode. We optimized the method using crude bacteria (Escherichia coli, Salmonella enterica, Shigella dysenteriae, Shigella boydii, Shigella flexneri, and Legionella pneumophila, Staphylococcus aureus) and yeasts (Candida albicans, C. kudriavzevii, and C. tropicalis).DiscussionThis approach opens the possibility of directly detecting microbial polysaccharides from clinical specimens. Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (LDI-TOF MS) using a specific self-ionizable ligand enables direct ionization without the need for an additional matrix, allowing for the particular detection of molecules of interest while suppressing the background signal.